Influence of kitchen waste compost and chemical fertilizer on the growth and yield of tomato (Solanum lycopersicum) (Journal of Biodiversity Conservation and Bioresource Management, 2022)
A pot experiment was conducted to evaluate the effect of kitchen waste compost (KWC) and NPK fertilizers on the growth and yield of tomato. It was laid out in a completely randomized block design (CRBD) using 25 treatments having 3 replications each. Agronomic parameters of the growth and yield of tomato were recorded at 15, 30, 45, and 60 days interval. The highest growth and yield parameter found with 60 days. The tallest plant height (57 cm) was recorded in T13(N120P60K80 kg ha-1 + 2.5ton KWC ha-1). Highest number of leaf found (17 per plant) in T18 (N30P15K20 kg ha-1 + 7.5 ton KWC ha-1) and T23 (N60P30K40 kg ha-1 + 10 ton KWC ha1. The length of midrib (22 cm) inT3 (5ton KWC ha-1) and dry weight of midrib (1.46 g plant-1) obtained topmost in T6(N30P15K20 kg ha-1). The girth of plants (1.4 cm) in T14: (N30P15K20 kg ha-1 + 5 ton KWC ha-1, and leaf area (5.61 cm2) in T2 (2.5 ton KWC ha-1). Total fresh weight of leaf, root and stem (60.3 g plant1) and dry weight of leaf, root and stem (21.91 g plant-1) were superior inT24(N90P45K60 kg ha-1 + 10 ton KWC ha-1), number of fruit per plant (10) inT5(10 ton KWC ha-1) and longest fruit (7.5 cm) inT5(10 ton KWC ha-1). Maximum fresh weight of tomato fruit (13.48 g plant-1) produces in T24 (N90P45K60 kg ha-1 + 10 ton KWC ha-1) and dry weight (5.32 g plant-1) in T20 (N90P45K60 kg ha-1 + 7.5 ton KWC ha-1). The findings revealed that KWC with NPK T24 (N90P45K60 kg ha-1 + 10 ton KWC ha-1) could be suggested to use for the maximum growth and yield of tomato. This trial has also been created the evidence that kitchen waste may be an alternative source of organic materials to produce tomato.J. Biodivers. Conserv. Bioresour. Manag. 2022, 8(1): 81-90